A GLIMPSE ON CLINICAL PERSPECTIVE OF SATMYA - Pavithra S; Darshan Babu N; Pampanna Gouda H (International Journal of Applied Ayurved Research, 2015)
Ayurveda is an ancient medical science where various principles are dealt for the chikitsa karma (treatment), where our acharyas have given much importance of knowledge obtained by pratyaksha (direct perception), anumana (inference), aptopadasha (testimony), and yukti (reasoning) during examination of patient for a successful treatment. pariksha is the process of examination which not only involves atura-pariksha (examination of patients) but also includes dravya pariksha (examination of medicinal drug and preparations), roga-pariksha (examination of disease) etc. The concept of satmya is dealt under dasha vidha atura pariksha (tenfold examination) and satmya is an important concept in both swastha-rakshana (maintenance of health) and aturasya vikara prashamana (treatment of disease). The concept of satmya is explained by different acharyas elaborately in their own way. The process of adopting satmya from asatmya is well explained in classics. Aims and objectives: To highlight the importance of satmya explained in different samhitas. Materials and methods : compiling the importance of satmya from different treatises. Conclusion: knowledge of satmya for diagnosis of the disease and planning of treatment plays vital role.